Asymmetric Monetary Policy Rules for an Open Economy: Evidence from Canada and the Uk. (17th February 2016) - Caglayan, Mustafa; Jehan, Zainab; Mouratidis, Kostas
Abstract: We present an analytical framework to examine the open economy monetary policy rule of a central bank under asymmetric preferences. The resulting policy rule is then empirically examined using quarterly data with regard to Canada and the UK from 1983q1 to 2007q4. Our empirical investigation shows that the open economy policy rule receives support from the data and that the monetary policy makers in the UK and Canada have asymmetric preferences. Robustness checks based on model calibration provide support for the suggested policy rule. Copyright © 2016 John Wiley & Sons, Ltd.